From the experience of SC TOMA SRL Călărasi county on autumn rape crop technology - Georgiana Crudu; Marin Toma (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
The company SC TOMA LTD is wholly owned private capital company, created and operating under the Law 31/1990. The company is located in Modelu commune, Calarasi county having in operation currently an area of 360 hectares of arable land. The technology represents all methods and procedures used for obtaining the particular product. The term technology refers to both the technical aspects and the economic ones, transposing them into practice. In fact the technology has two distinct sides or distinct parties in interdependence: the technical side and the economic side. The technical side is considering the means and works to provide conditions for plant growth and development according to their requirements in order to obtain higher productions per unit area. The economic side aims the parameters of efficiency of the technology both on each segment or link of it, as well as a whole.
Keywords: 330; technology of rape crop; rapeseed varieties and hybrids; bio stimulator; average productions; selling prices